Uncovering the Unheard Voices on the Need for Tourism Literacy in Samota Special Economy Development Zone of Sumbawa Island - Henny Soepriyanti; Untung Waluyo; Muhammad Amin; Eka Fitriana (Yayasan Keluarga Guru Mandiri, 2023)
The diversity of customs and culture of the people of Sumbawa is not widely known to foreign and domestic visitors because of the unavailability of tourism literacy products. This study aims to analyze and describe sources of tourism literacy in Sumbawa Island, focusing on providing information pertaining to tradition, daily life, history, and community perspectives. This current issue has not been explored as a potential source for developing tourism literacy. The present study employed a descriptive, qualitative methodology with an ethnographic design. The study finds that stakeholders in the Samota area still lack written literacy sources for official information for visitors visiting Sumbawa. This lack of literacy sources makes visitors unaware of each destination's conditions and customary rules. The study concludes that the development of tourism literacy at the research location needs to be done immediately by involving the community of tourism actors to ensure compatibility between government programs and sustainable community-based tourism development. While the direct link between tourism literacy and scientific research may not be immediately evident, the present study can contribute to a deeper understanding of cultural preservation, public engagement, economic support, and knowledge exchange in various disciplines.